Internet of things based mobile application to improve citizen security - Yulihño Ochante-Huamaccto; Francis Robles-Delgado; Fernando Sierra-Liñan; Michael Cabanillas-Carbonell (Institute of Advanced Engineering and Science, 2022)
Citizen insecurity is a social problem that has increased considerably around the world. To combat it, in this research a mobile application based on IOT has been developed with the objective of mapping crimes and incident alerts to improve citizen security. Scrum methodology was used and a significant improvement can be seen with respect to the following indicators: number of reports of dangerous places, with an increase of 102.7%; the second indicator: number of reports by type of crime, with an increase of 25.34%; and the indicator: response time to attention, with an increase of 23.5%. It is determined that there is a significant positive influence of the mobile application developed to improve citizen security.